Privatization in the UK Facts and Figures - Curwen J. Ptert (United Kingdom: Ernst &Young, 1994)
This book ia meant to serve as a guide to the techniques, terminology and overall strategy to UK privatization programme.
Includes bibliograghy.
gp. 25/01/2019
Loan
Keywords: Economic conditions; Privatization; United Kingdom